2006
DOI: 10.1002/pmic.200600303
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of bronchoalveolar lavage in lung diseases

Abstract: The proteomic approach is complementary to genomics and enables protein composition to be investigated under various clinical conditions. Its application to the study of bronchoalveolar lavage (BAL) is extremely promising. BAL proteomic studies were initially based on two-dimensional electrophoretic separation of complex protein samples and subsequent identification of proteins by different methods. With the techniques available today it is possible to attain many different research objectives. BAL proteomics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 130 publications
(156 reference statements)
3
74
0
Order By: Relevance
“…However, this approach suffers from large variations caused by sample preparation, protein loading, and gel staining (38). Another limit of 2DE for proteomics concerns the poor recovery of proteins from the gel for MS. Methods to supplement or replace 2DE, such as multidimensional LC have therefore been sought (39).…”
Section: Discussionmentioning
confidence: 99%
“…However, this approach suffers from large variations caused by sample preparation, protein loading, and gel staining (38). Another limit of 2DE for proteomics concerns the poor recovery of proteins from the gel for MS. Methods to supplement or replace 2DE, such as multidimensional LC have therefore been sought (39).…”
Section: Discussionmentioning
confidence: 99%
“…Several articles have been published on the proteomic composition of human BALF, especially for adults (9)(10)(11)(12). Among detected proteins that are receiving further attention, especially for their function and involvement in acute and chronic inflammatory conditions, are the α-defensins and S100A member proteins (calgranulins) (13,14).…”
mentioning
confidence: 99%
“…Numerous reports have described increased oxidation with aging and have postulated a causal relationship between this increase and age-related pathologies (5,41,50,56). Increased oxidation of BAL proteins has been shown to occur in sarcoidosis, pulmonary fibrosis, and emphysema (28,34,47,56). Furthermore, using a newly improved multiplex immunoblotting approach, we showed that the increases in oxidation (carbonylation) were not random and that some proteins were preferentially oxidized.…”
Section: Discussionmentioning
confidence: 56%